Reflective Journal Writing: Writing Processes Applied by Skilful and Less Skilful EFL Graduate Students - S. Arifin (Jurnal Pendidikan dan Pengajaran, 2021)
Reflective writing (RW) is one of the most common writing activities adopted by higher education students. However, some still struggle with this writing technique. Therefore, this study aims to analyze the appropriate process/sub-process used by skilled and less skilled EFL graduate students in doing Reflective writing. Data were collected from 2 (two) post-graduate students through think-aloud, observation, retrospective, and semi-structured interviews. The instrument used to collect data is a questionnaire. The data analysis technique used is descriptive qualitative and quantitative analysis. The result of the research is some students have difficulty in reflective writing. A helpful solution is to encourage students to practice writing in various contexts under different environments and receive ongoing training supported by the teacher. The importance of integrating a focus on effective writing processes/sub-processes in academic writing and encouraging students to practice Reflective essays in various contexts by reading extensively while writing reflections. In addition, when the reflection writing task is carried out regularly, it helps students to have adequate knowledge of essential concepts and critically understand them.